THE FACTORS THAT AFFECT FACTORS THAT AFFECT THE EXISTENCE OF AGRICULTURAL FARMER GROUPSTHE EXISTENCE OF AGRICULTURAL FARMER GROUPS (A Study in Kel. Cempaka Permai, Kec. Gading Cempaka, Kota Bengkulu): A Study in Cempaka Permai Village, Gading Cempaka Sub-district, Bengkulu City) - Cahyadi , Ghani Setiawan; Yuristia, Rahmi (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
The objectives of this research are 1) To find out the group dynamics in farmer groups in Cempaka Permai Village, Gading Cempaka Sub-district, Bengkulu City, 2) To find out the agricultural extension in farmer groups in Cempaka Permai Urban-Village, Gading Cempaka Sub-district, Bengkulu City 3) To find out the existence of farmer groups in Cempaka Permai Village, Gading Cempaka Subdistrict, Bengkulu City 4) To analyse the factors that affect the existence of farmer groups in Cempaka Permai Village, Gading Cempaka Subdistrict. This research was conducted purposively in Cempaka Permai Village, Gading Cempaka Sub-district, Bengkulu City, involving 60 farmer group members as respondents. Data analysis used the descriptive qualitative analysis method, Likert scale, and Partial Least Square (PLS). The analysis results show that the dynamics of farmer groups significantly impact the existence of farmer groups. In contrast, the role of extension workers has no significant impact on the existence of farmer groups. The research findings highlight the interplay between internal group dynamics and external support in fostering farmer groups' success and continued existence. This research recommended that farmers' groups focus on internal and external government support mechanisms; the policy is needed to strengthen farmer groups, leading to improved livelihoods for individual farmers and a more robust agricultural sector.